Intra-amniotic Digoxin for Fetal Anomaly in Second and Early Third Trimester - Shakya, B; Chaudhary, P; Tumbahangphe, M; Jha, M (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: Carrying a baby with major anomaly is emotional trauma for mother and her family. If born alive, these babies would either not survive or would have significant disability. The objective of this study was to induce fetal demise by instillation of digoxin intra-amniotically for fetal anomaly before termination of pregnancy. Methods: This was a cross-sectional study undertaken at Paropakar Maternity and Women’s Hospital from April 13, 2012 to October 13, 2013. Patient characteristics, gestational age, types of fetal anomaly and its time of detection were recorded in 32 cases with fetal anomaly in second and early third trimester. One milligram digoxin was instilled intra-amniotically under ultrasound guidance and after 24 hours, ultrasonography was done to check fetal cardiac activity. Induction of labour using misoprostol as per FIGO guideline and augmentation with oxytocin was done if already in labour. Induction to delivery interval, effectiveness and side effects of digoxin were recorded. Results: Among 32 cases of fetal anomaly, majority occurred in primigravida (n=17, 53.12%). The mean age was 25 years and mean gestational age was 26.5 weeks’. Majority of them were anencephaly (n=16, 50%) followed by multiple anomaly (n=6, 18.75%). Thirty one (96.87%) cases visited out-patient department, 25% of them had presented late at 30-34 weeks’. Following 24 hours of intra-amniotic digoxin, cardiac activity was absent in all cases and there was no side effect of digoxin. Spontaneous expulsion occurred in 9.37%, oxytocin augmentation (n=6, 18.75%) and misoprostol induction (n=23, 71.87%). The mean induction to delivery interval was 47.3 hours. Conclusions: Intra-amniotic digoxin instillation appeared safe and effective in inducing fetal demise for fetal anomaly in second and early third trimester. DOI: http://dx.doi.org/10.3126/njog.v9i1.11188 NJOG 2014 Jan-Jun; 2(1):48-51